2021
DOI: 10.48550/arxiv.2104.08168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing Cosmic Dawn : Ages and Star Formation Histories of Candidate $z\geq$9 Galaxies

N. Laporte,
R. A. Meyer,
R. S. Ellis
et al.

Abstract: We discuss the spectral energy distributions and physical properties of six galaxies whose photometric redshifts suggest they lie beyond a redshift 𝑧 9. Each was selected on account of a prominent excess seen in the Spitzer/IRAC 4.5𝜇m band which, for a redshift above 𝑧 = 9.0, likely indicates the presence of a rest-frame Balmer break and a stellar component that formed earlier than a redshift 𝑧 10. In addition to constraining the earlier star formation activity on the basis of fits using stellar population… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…These galaxies thus first hinted at a trend of larger Ly𝛼 fractions in more luminous galaxies at 𝑧 > 7 compared to fainter sources (see also Ono 2012;Mason et al 2018). This has subsequently been confirmed with larger statistics (e.g., Jung et al 2020;Endsley et al 2021b;Laporte et al 2021), albeit not all luminous sources at 𝑧 > 7 revealed detectable Ly𝛼.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…These galaxies thus first hinted at a trend of larger Ly𝛼 fractions in more luminous galaxies at 𝑧 > 7 compared to fainter sources (see also Ono 2012;Mason et al 2018). This has subsequently been confirmed with larger statistics (e.g., Jung et al 2020;Endsley et al 2021b;Laporte et al 2021), albeit not all luminous sources at 𝑧 > 7 revealed detectable Ly𝛼.…”
Section: Introductionmentioning
confidence: 64%
“…While other particularly distant EoR galaxies have been spectroscopically confirmed since the discovery of these sources in the EGS field (e.g. Oesch et al 2016;Jiang et al 2021;Hashimoto et al 2018;Jung et al 2020;Laporte et al 2021), they still rank among the most distant detected Ly𝛼 emission lines (see also Larson et al, in prep;Larson et al 2020). For more information on the luminous Ly𝛼 sources, see Section 3.1 and Tables 1 and 2.…”
Section: Dedicated Follow-up Of Luminous High-redshift Sourcesmentioning
confidence: 99%
“…The light green hexagons indicate the U V luminosities and redshifts for other z > 6 sources with spectroscopic redshift determinations from ALMA. The solid and open blue circles are sources with redshift measurements from ≥ 7σ and <7σ Lyα lines, respectively (Vanzella et al 2011;Shibuya et al 2012;Ono et al 2012;Schenker et al 2012;Pentericci et al 2012;Jiang et al 2013;Sobral et al 2015;Zitrin et al 2015;Song et al 2016;Stark et al 2017;Hoag et al 2017;Larson et al 2017;Pentericci et al 2018;Fuller et al 2020;Jung et al 2020;Endsley et al 2021;Pelliccia et al 2021;Laporte et al 2021).…”
Section: Characteristics Of the Rebels Targetsmentioning
confidence: 99%
“…Combining the non-detections with other results from the literature, the analysis found that the fraction of Lyα emitters amongst samples of Lymanbreak galaxies decreased by a factor of ∼ 3× from z ∼ 6 to z ∼ 8 (only ∼ 300 Myrs of evolutionary time), attributable to an increasingly opaque neutral medium. While some recent results of especially luminous z ∼ 8 galaxies (e.g., Finkelstein et al 2015;Oesch et al 2015;Zitrin et al 2015;Roberts-Borsani et al 2016;Laporte et al 2017;Stark et al 2017;Hashimoto et al 2018;Laporte et al 2021) have begun to challenge this pic-ture with unexpected detections of Lyα in objects with a large Spitzer /IRAC 3.6 µm minus 4.5 µm excess, such galaxies come from small area surveys (e.g., CANDELS or Frontier Fields clusters) that are prone to cosmic variance (and clustering) effects and whether their extreme properties are representative of the z 8 general population is subject to debate. The observations presented here and in Treu et al (2013) are likely more robust to cosmic variance effects due to their (pure-)parallel selection and are more consistent with an especially opaque IGM at z ∼ 8.…”
Section: Keck/mosfire Observationsmentioning
confidence: 99%
“…Such a process is thought to occur over the first billion years of the Universe (corresponding approximately to redshifts of z ∼ 6), thus making the detection and characterization of galaxies at those epochs a prerequisite. To this end, the last decade has seen remarkable progress in enlarging z 6 galaxy samples to their thousands, in large part thanks to the highly sensitive near-infrared (NIR) capabilities of the Hubble Space Telescope's (HST ) Wide Field Camera 3 (WFC3) and ground-based spectroscopic efforts, revealing hundreds of sources at redshifts of 7 < z < 8 (e.g., Bradley et al 2012;Bowler et al 2014;Schmidt et al 2014;Bouwens et al 2015;Finkelstein et al 2015;Laporte et al 2017;Stefanon et al 2017) and a dozen sources out to redshifts as high as 9 < z < 11 (e.g., Coe et al 2013;Ellis et al 2013;Oesch et al 2014Oesch et al , 2016Oesch et al , 2018Hashimoto et al 2018;Bouwens et al 2019;Bowler et al 2020;Laporte et al 2021).…”
Section: Introductionmentioning
confidence: 99%